A SARS-CoV-2 outbreak in a plastics manufacturing plant - Alice Graham; Amber I. Raja; Karin van Veldhoven; Gillian Nicholls; Andrew Simpson; Barry Atkinson; Ian Nicholls; Hannah Higgins; Joan Cooke; Allan Bennett; Derek Morgan; Chris Keen; et al. (BMC, 2023)
Abstract Background A SARS-CoV-2 outbreak with an attack rate of 14.3% was reported at a plastics manufacturing plant in England. Methods Between 23rd March and 13th May 2021, the COVID-OUT team undertook a comprehensive outbreak investigation, including environmental assessment, surface sampling, molecular and serological testing, and detailed questionnaires, to identify potential SARS-CoV-2 transmission routes, and workplace- and worker-related risk factors. Results While ventilation, indicated using real-time CO2 proxy measures, was generally adequate on-site, the technical office with the highest localized attack rate (21.4%) frequently reached peaks in CO2 of 2100ppm. SARS-CoV-2 RNA was found in low levels (Ct ≥35) in surface samples collected across the site. High noise levels (79dB) were recorded in the main production area, and study participants reported having close work contacts (73.1%) and sharing tools (75.5%). Only 20.0% of participants reported using a surgical mask and/or FFP2/FFP3 respirator at least half the time and 71.0% expressed concerns regarding potential pay decreases and/or unemployment due to self-isolation or workplace closure. Conclusions The findings reinforce the importance of enhanced infection control measures in manufacturing sectors, including improved ventilation with possible consideration of CO2 monitoring, utilising air cleaning interventions in enclosed environments, and provision of good-quality face masks (i.e., surgical masks or FFP2/FFP3 respirators) especially when social distancing cannot be maintained. Further research on the impacts of job security-related concerns is warranted.